Out of sight, out of mind?! Stakeholderspecific evaluation and acceptance of underground HVDC cables - Mauelshagen, Christine; Jakobs, Eva-Maria (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
A successful energy turnaround – the so-called Energiewende – requires the reinforcement and expansion of the electricity grid. In late 2015, the German government approved a law prioritizing the use of underground cables over overhead lines near residential areas in order to speed up the grid expansion and to minimize local resistances. This paper deals with the perception and acceptance of concerned parties regarding an underground cable project planned in a rural area (Rheinisches Braunkohlerevier). By means of qualitative interviews the perspectives of local farmers and residents on the Energiewende, acceptance and evaluation of the grid expansion in general as well as the planned underground cable project and its ancillary facilities which are to be implemented in the living environment of the two affected parties were investigated and compared. The results show group-related similarities and differences. Overall, both groups were found to have a positive attitude towards the Energiewende and a preference for underground cables compared to overhead lines. However, criticism towards both issues was also voiced. Despite the general preference for underground cables, local residents evaluate the particular underground cable project in the investigated region rather neutral, partly indifferent, and in some aspects critical. In contrast, the attitude of local farmers is rather critical due to a multitude of perceived disadvantages, which partially lead to (active) acts of resistance that could slow down the project. It becomes obvious that regional site characteristics, spatio-temporal processes, habit-forming effects as well as experience and knowledge play a substantial role when evaluating the planned underground cables and that these aspects should be considered when planning grid infrastructure projects.